Spatial and temporal analysis of severe fever with thrombocytopenia syndrome in Zhejiang Province, China, 2011 - 2015 - Fudong Li; Fan He; Jimin Sun; Yujia Zhai; Jianmin Jiang; Junfen Lin (Journal of Infection in Developing Countries)
Introduction: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease first discovered in northeast and central China in 2009, and SFTS cases increased year by year in China. This study aimed to identify the spatial and temporal clusters of SFTS in Zhejiang Province, China.